2021
DOI: 10.1177/10731911211020114
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mothers’ Automatic Affective and Discipline Reactions to Child Behavior in Relation to Child Abuse Risk: A Dual-Processing Investigation

Abstract: Given the scope and adverse clinical consequences of child abuse, assessment of salient etiological factors can lend critical insights needed for abuse prevention. Increasingly, dual-processing models have been applied to aggression, which postulate that parallel automatic and conscious processes can evoke aggressive behavior, implicating both affective and cognitive elements in both routes. Using two samples of mothers ( n = 110 and n = 195), the current investigation considered evidence of the reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Although parents’ personal stress and anxiety has received empirical attention as a risk factor for maltreatment risk during the pandemic (Kerr et al, 2021 ; Lee, Ward, Chang et al, 2021 ; Patrick et al, 2020 ), whether parents were worried about their children’s behavior (Li & Zhou, 2021 ) has not been adequately targeted as a specific, proximal contributor to child maltreatment risk. Research to date has rarely considered the role of parental worry regarding children’s behavior as an additional affective factor independent of anger that contributes to physical maltreatment risk (Pinderhughes et al, 2000 ; Rodriguez, Silvia et al, 2021 ). The current investigation indicated that maternal worry about children’s behavior was related not only to their perceived increased physical aggression toward their child since the pandemic began but to maternal self-report of neglectful behavior as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although parents’ personal stress and anxiety has received empirical attention as a risk factor for maltreatment risk during the pandemic (Kerr et al, 2021 ; Lee, Ward, Chang et al, 2021 ; Patrick et al, 2020 ), whether parents were worried about their children’s behavior (Li & Zhou, 2021 ) has not been adequately targeted as a specific, proximal contributor to child maltreatment risk. Research to date has rarely considered the role of parental worry regarding children’s behavior as an additional affective factor independent of anger that contributes to physical maltreatment risk (Pinderhughes et al, 2000 ; Rodriguez, Silvia et al, 2021 ). The current investigation indicated that maternal worry about children’s behavior was related not only to their perceived increased physical aggression toward their child since the pandemic began but to maternal self-report of neglectful behavior as well.…”
Section: Discussionmentioning
confidence: 99%
“…The measure was developed to assess negative child attributions and punishment intentions. In a recent expansion of the PCV (Rodriguez, Silvia et al, 2021 ), questions following the vignettes were expanded to include reports of emotion the parent would feel in response to the scenario—the only known measure to assess both parental anger and worry regarding children’s behavior. For each vignette, the mother indicated her level of anger in response to the scene, from 1 ( not angry or frustrated at all ) to 9 ( very angry or frustrated ), as well as indicating her level of worry about her child from 1 ( not worried about my child at all ) to 9 ( very worried about my child ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation